A framework for recovering waste heat energy from food processing effluent - Luo, Yang; Jagtap, Sandeep; Trollman, Hana; Garcia-Garcia, Guillermo (MDPI, 2023)
Effluent water from food processing retains considerable heat energy after emission from treatment systems. Heat recovery technologies that may be appropriate for implementation in the food processing industry have been widely explored, and selection of the most suitable methodologies has been pursued. A four-stage framework is introduced in this paper to evaluate the potential recoverability of waste heat along with acceptor streams. The systematic approach utilizes thermal and temporal compatibility tools and cost–benefit analyses to determine the ideal heat-recovery equipment for food processing effluent. The applicability of this framework is demonstrated through an industrial case study undertaken in a vegetable canning processing facility. Based on the findings, the framework yields an efficient and optimized heat recovery approach to reducing the total energy demand of the facility.
Keywords: heat recovery; effluent water; decision support system; structured approach